Tingkat Profitabilitas Pembiayaan Mikro dan Metode Economic Value Added: Studi Pada Bank BRI Syariah - M Nur Rianto Al Arif; Suci Hanifa (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
Microfinance is one of the Islamic bank's products for micro, small, and medium enterprises. The aim of this research is to analyze the profitability ratio in microfinance using the economic value-added method. The object of this study is at Bank of BRI Sharia. The result shows that in 2014 had an economic value added (EVA) of about Rp 327.030.746.600 or about 10,48% from the financing. The EVA's value shows that the microfinance at Bank of BRI Sharia had good enough. The implication of this result is Bank of BRI Sharia should maintain and increase the quality of the financing strategy in microfinance products.